High‐Temperature Annealing of AlGaN. Issue 23 (7th October 2020) - Hagedorn, Sylvia; Khan, Taimoor; Netzel, Carsten; Hartmann, Carsten; Walde, Sebastian; Weyers, Markus
Abstract : In the past few years, high‐temperature annealing of AlN has become a proven method for providing AlN layers with low dislocation densities. Herein, the example of Al0.77 Ga0.23 N is used to investigate whether annealing can also improve the material quality of the ternary alloy. A detailed analysis of the influence of annealing temperature on structural and optical material properties is presented. It is found that with increasing annealing temperature, the threading dislocation density can be lowered from an initial value of 6.0 × 10 9 down to 2.6 × 10 9 cm −2 . Ga depletion at the AlGaN surface and Ga diffusion into the AlN buffer layer are observed. After annealing, the defect luminescence between 3 and 4 eV is increased, accompanied by an increase in the oxygen concentration by about two orders of magnitude. Furthermore, due to annealing optical absorption at 325 nm (3.8 eV) occurs, which increases with increasing annealing temperature. It is assumed that the reason for this decrease in ultraviolet (UV) transmittance is the increasing number of vacancies caused by the removal of group‐III and N atoms from the AlGaN lattice during annealing. Abstract : Annealing of Al0.77 Ga0.23 N at temperatures up to 1705 °C results in a reduction of the threading dislocation density. This is accompanied by reduced Ga content at the surface and at the interface to the AlN buffer and increased O content by diffusion from the sapphire substrate. Absorption bands around 320 nm are formed.